Islamic Philantropy Adaptation Towards Financial Social Exclusion Among Independen Oil Palm Smallholder - Khairul Anwar Mohd Nor; Mohd Adib Ismail; Muhammad Hakimi Mohd Shafiai; Khairunnisa Hasbullah; Mohd Noor Mohd Ali (Faculty of Economic and Business, 2022)
Social exclusion among independent smallholders of the oil palm sector is a socioeconomic problem that is closely linked to the incidence of poverty and economic inequality. Although there are several Islamic banking institutions that provide micro credit to the farmers, but not received much response due to lack of attractiveness and non-competitive features especially to independent smallholder. Therefore, other channels like philanthropy are seen as an alternative for smallholder empowerment in the form of integration between zakat business capital, and business incubators as mechanisms to address these issues. The objective of this study is to examine the role of Islamic philanthropic instruments of zakat and waqf in addressing the problem. The methods used in this study are based on qualitative approach like research interviews, observations, written expert experiences, and research publications. The findings provide valuable insights for stakeholders into Islamic philanthropy role and the importance of exposure in improving ISH performance, which could help them in (re-) align their agricultural practices and formulating strategies for industry player’s guidance.JEL Classification: A13, G21, J24, Q02, Z12